Densities of n-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid (TAPS) + glycol (DEG / TEG / T4EG) + water - De Jesus, Medarlo B. (Animo Repository, 2020)
In this present work, density of ternary system containing n-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid (TAPS), glycol, and water was presented. The considered glycols are diethylene glycol (DEG), triethylene glycol (TEG), and tetraethylene glycol (T4EG). The measurements were done over a temperature range of 298.15 to 343.15 K at normal atmospheric pressure. Different concentrations (4 to 16 % by weight TAPS or 56 to 44 % water, in a fixed amount of glycol - 40 %) were used. The effects of temperature and compositions on the measured properties were discussed and then correlated based on the equation proposed for aqueous salt-glycol systems. Calculation results show that the applied model was satisfactory in representing the measured property of the considered ternary aqueous solutions containing TAPS and glycol. © Published under licence by IOP Publishing Ltd.